Submission of evidence on the disproportionate impact of Covid-19 on grassroots football: An agenda to protect our game and communities - Parnell, D.; Fitzpatrick, D.; Cockayne, D.; Drywood, E.; Widdop, P. (2020)
The COVID-19 crisis provides the impetus to fundamentally reconsider the structure and priorities of English football. COVID-19 has revealed the fragile nature of the football ecosystem in England and the unsustainable business models that pervade the football pyramid. The key stakeholders in football need to re-think the relationship between professional football clubs, grassroots football and the wider community, given its significant economic and social contribution. Grassroots football is in decline. A return to play is not enough. This aspect of football requires significant investment to ensure quality experiences and participation goals are met. In England, grassroots or community football is not only the most popular sport, but it is also a significant contributor to economic, social and public health outcomes. COVID-19 could present a tipping point for an already declining grassroots game. Playing sport is a significant driver in the realisation of children's rights and well-being. Football presents a unique opportunity in the lives of young people to improve their health, to access training and education, and to develop social capital. The removal of informal and more structured opportunities to play football, particularly at the grassroots, can have a significant detrimental effect on children's mental and physical well-being, as well as impact resources embedded in social networks. Robust political leadership is urgently needed to protect grassroots football in the short term, to ensure its future sustainability. This moment of reflection also represents an opportunity to arrest the decline in the number and quality of playing surfaces due to central and local government mismanagement, which has been accelerated during the past decade of austerity